Teachersâ Perceptions towards the Usage of Courseware in the Teaching and Learning of Economics at Malaysian Secondary Schools - Ranjit Singh, Termit Kaur; Mohamed, Abdul Rashid (EDUCARE, 2010)
ABSTRACT: This purpose of study was to identify teachersâ perceptions towards the usage of courseware in the teaching and learning of Economics at Form 4 and Form 5 levels at Penang secondary schools. Other aspects observed were the knowledge and basic skills of the teachers in the use of computer, the methods used in the teaching and learning of Economics and their perceptions towards the use of courseware in the teaching and learning process. In this study, 30 in-service teachers were chosen randomly as research samples, representing the teachersâ population teaching Economics in 96 schools in Penang. This study was carried out using the quantitative approach. Descriptive statistics used include frequency, %age, and min relativity index. The findings showed that teachers teaching Economics at Penang secondary schools are receptive about the usage of courseware in the teaching and learning of Economics. They also believed that the usage could also bring benefits to the students. The results of the overall relativity index show that there is readiness among the teachers in using courseware in the teaching and learning of Economics at the Form 4 and Form 5 levels. A few suggestions for improvements in the teaching and learning process have also been put forth in this paper.KEY WORDS: Teachersâ perceptions, courseware, economics, knowledge and basic skills, computer, and teaching and learning process.Â Â About the Authors: Termit Kaur Ranjit Singh and Abdul Rashid Mohamed are the Lecturers at the School of Educational Studies USM (Science University of Malaysia), Pulau Pinang, Malaysia. One of them can be reached at: termitk@usm.myHow to cite this article? Ranjit Singh, Termit Kaur & Abdul Rashid Mohamed. (2010). âTeachersâ Perceptions towards the Usage of Courseware in the Teaching and Learning of Economics at Malaysian Secondary Schoolsâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.23-34. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 20, 2010); Revised (July 20, 2010); and Published (August 17, 2010).